Quantitative MRI and EMG study of the brachial plexus - Mahbub, Zaid Bin (2014)
This thesis describes the development and applications of quantitative MRI and combined EMG and MRI study of Brachial Plexus. The protocols developed in this thesis have been used on normal healthy subjects, aiming at characterizing the tissues based on their MR and EMG parameters. The Brachial Plexus is the upper portion of the peripheral nervous system and controls the movements of shoulder and arms. Neurological disorders in the brachial plexus can result from cervical spondylotic neuropathy due to compression of nerve roots exiting from vertebra or compression of the spinal cord due to bulging discs. MRI provides the opportunity to obtain precise information on the location of these disorders and to provide quantitative biomarkers. EMG in the form of the distribution of F-latency (DFL) is a recently introduced nerve conduction parameter that can detect functional symptoms with such disorders.